Evaluasi Pelayanan Program Inovasi "POS KAMLING" (Pelayanan On The Spot Kecamatan Keliling) di Kecamatan Gedangan Kabupaten Sidoarjo - Putri Rahma Sari; Tukiman Tukiman (Public Service and Governance Journal, 2025)
The on the spot mobile sub-district service program (POSKAMLING) is an innovative service in Gedangan sub-district, Sidoarjo Regency which aims to bring direct services closer to the community in the form of mobile services. This article aims to determine the Evaluation of the POSKAMLING Program (On The Spot Mobile Sub-district Service) in Gedangan Sub-district, Sidoarjo Regency. The problem is focused on Program Evaluation. The data analysis uses Milles' analysis technique. Hubernman and Salda 2014. The theoretical reference used is William N Dunn's theory (2003), which consists of Effectiveness, Efficiency, Adequacy, Leveling, Responsiveness, and Accuracy. The informants of this study involved key informants including the Gedangan Sub-district Computer Administrator and the Population and Civil Registration Service Staff in the Population Administration Information System Management Section. Based on the research results, the POSKAMLING Program is said to be very effective and efficient because the service makes it easier for the community. This program has proven to be right on target and satisfies community groups. However, in the efficiency criteria there are shortcomings and obstacles in the implementation of the POSKAMLING Program such as late delivery of forms. So that makes people wait a long time in the process of managing population documents.